Principles and Concepts of Emergency Nursing - Chellappan, Sheeba (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2020)
The nursing care of individuals of all ages with perceived physical or emotional alterations which are undiagnosed and may require prompt intervention. The scope of emergency nursing practice involves assessment, diagnosis, treatment and evaluation of perceived, actual or potential, sudden or urgent and physical or psychosocial problems that are primarily episodic or acute and occur in variety of setting. Emergency nursing requires a broad knowledge base to provide safe and competent care to the client with variety of conditions. The clinical nurse who functions inside the hospital’s emergency department requires specialized training in clinical aspect of emergency care.